Optimalisasi Persediaan Beras Pada Tingkat Distributor di Kota Bau-Bau Optimization ofRice Supply at DistributorLevel in The City of Bau-Bau - Antasalam Ajo; Marsuki Iswandi; Sitti Aida Adha Taridala (JURNAL PANGAN, 2012)
Penelitian ini bertujuan menganalisis optimalisasi persediaan beras pada tingkat distributor di Kota Bau-Bau, menggunakan data tahun 2010 sebagai acuan perencanaan persediaan pada tahun-tahun berikutnya. Data dianalisis menggunakan analisis deskriptif untuk melihat upaya-upaya yang dilakukan distributor. Model EOQ digunakan untuk menentukan jumlah dan saat  pemesanan yang tepat agar total biaya minimal. Model perputaran persediaan digunakan untuk menganalisis lama modal tersimpan dalam persediaan, dan model regresi non-linier sederhana diterapkan untuk melakukan peramalan penjualan. Kesimpulan penelitian adalah: (i) upaya-upaya distributor dalam mengeloia persediaan beras adalah pemesanan sebelum stok habis, pembayaran ke supplier setelah beras tiba, dan selalu jujur dan saling percaya; (ii) jumlah pemesanan distributor rata-rata adalah 304,18 ton, ketika persediaan rata-rata adalah sebanyak 9,34 ton, dan biaya total minimal rata-rata adalah Rp 9.869.222; (iii) perputaran persediaan beras minimal 6kali setahun; dan (iv) peramalan penjualan distributor bulanan untuk Januari hingga Juni tahun 2011 rata-rata sebanyak 56,38 ton, dan jumlah pemesanan periode dua bulanan rata-rata sebesar 112,69 ton.This study isaimed at analyzing the optimization ofrice provision at distributor level in Bau-BauMunicipality using the 2010 data as a basis for planning the provision in the following years. This is an explanatory study in which the data are gathered through a survey method. The population ofthe study is 8 rice distributors. The data are analyzed using a descriptive method to identify some endeavors done by the distributors. The EOQ model is used to determine the number and time of fixed orders to minimize costs. The model ofprovision rolling is usedto analyze the time length for the capital put in stock and the simple nonlinear regression is used to predict the selling based on the data ofmonthly selling in 2010. This study shows the following findings. First, the efforts made by rice distributors are able to optimize the rice provision although some improvement is still needed. These include orders that should be placed before stock off, payment that ismade right after delivery and honesty and trustworthy that is encouraged to build among suppliers and distributors. Second, the total maximum order for each distributor ranges from 153.63 to 532.68, averaging of304.18tons ofrice. This maximum order ismade when stocks reach about 4.45 up to 21.78 tons, averaging of9.34tons. The total minimum costvaries about Rp 4,893,690, up to Rp 17,894,090, averaging ofRp 9,869,222. Third, the rolling ofrice provision is atminimum of6 times per year. Fourth, the distributor estimate is in the average of56.38tons for the monthly selling between January and June 2010. The selling estimate by each distributoris in the average of56.38tons. The total order for each two months ranges from 111.01 up to 114.31 averaging of 112.69 tons,